Modelling of Data Communication over Medium-Voltage Power Distribution Lines - Jaromir Hrad; Jiri Vodrazka (Communications, 2016)
The paper is dedicated to different topologies of medium-voltage power distribution lines with respect to their properties influencing the transmission of communication signals. We provide very basic introduction to the problems of signal transmission over these lines, discuss their parameters and examine the typical behaviour and characteristics. We conclude our considerations with some specific recommendations concerning the most advantageous configurations for the purposes of Power Line Communication (PLC). The data transmission capacity is calculated for different topologies and network conditions.